Comparison of the insecticide susceptibilities of laboratory strains of Aedes aegypti and Aedes albopictus - Gómez, Andrea (2011)
A susceptible strain of Aedes albopictus derived from the Gainesville strain (Florida, USA) was established in our laboratory. The larvicidal efficacies of the neurotoxic insecticides temephos, permethrin and the pure cis and trans-permethrin isomers and the microbial insecticide Bacillus thuringiensis israelensis (Bti) against Ae. albopictus were estimated and compared to a susceptible strain of Aedes aegypti. The larvicidal effect of insect growth regulator pyriproxyfen was also evaluated in both mosquito strains. The median lethal concentration/median emergency inhibition values for Ae. aegypti and Ae. albopictus, respectively, were: temephos, 3.058 and 6.632 ppb, permethrin, 3.143 and 4.933 ppb, cis-permethrin, 4.457 and 10.068 ppb, trans-permethrin, 1.510 and 3.883 ppb, Bti, 0.655 and 0.880 ppb and pyriproxyfen, 0.00774 and 0.01642 ppb. Ae. albopictus was more tolerant than Ae. aegypti to all six larvicides evaluated. The order of susceptibility for Ae. aegypti was pyriproxyfen > Bti > trans-permethrin > temephos > permethrin > cis-permethrin and for Ae. albopictus was pyriproxyfen > Bti > trans-permethrin > permethrin > temephos > cis-permethrin. Because both species can be found together in common urban, suburban and rural breeding sites, the results of this work provide baseline data on the susceptibility of Ae. albopictus to insecticides commonly used for controlling Ae. aegypti in the field.